ANALYSIS OF THE CONSTRAINT EFFECT AND CREEP CRACK INITIATION TIME FOR STRUCTURE WITH ЕMBEDDED CRACKS - LI YuPeng; LI WenPeng; LI DingHe; WU DongQuan; WANG YuFeng; ZHENG YuXiang (Jixie qiangdu)
The specimen structure with embedded cracks served at elevated temperature was studied. The constraint effect and creep crack initiation time were analysed using the ductility exhaustion approach by 3D finite element method. The results revealed that the max value of constraint parameter was located at the end of major axis of elliptical crack, and the constraint levels enlarge with increasing the crack length or the crack depth, which meant that embedded cracks with a larger a/t or a/c would suffer from worse condition of stress concentration and there would be more dangerous. Besides, for the creep crack initiation times, the structure with a larger a/t or a/c or loadings would accompany high crack driving force under creep condition, which could cause a shorter period to creep cracking initiation, as well as a smaller creep crack initiation time. Additionally, a prediction equation and engineering method of the constraint parameters and creep crack initiation time for embedded cracks was proposed, and the prediction method of creep crack initiation time was validated.